Brentuximab vedotin (Adcetris®) in therapy of system anaplastic large cell lymphoma. Case report - A. A. Semenova; P. A. Zeynalova; M. S. Nikitina; M. I. Akhmedov (Онкогематология, 2019)
The introduction of new monoclonal antibodies has become an integral part of the treatment of malignant tumors.Brentuximab vedotin (Adcetris®) – anti-D30 monoclonal antibody conjugated with monomethyluristatin E – has become a new drug registered since February 2016 in the Russian Federation (SGN-35; Adcetris®). The Food and Drug Administration approved the Adcetris® since August 2011 as a therapy for refractory/recurrent Hodgkin’s lymphoma and anaplastic large cell lymphoma.This article describes the clinical case of successful use of Brentuximab vedotin, accompanied by the development of a rare complication – tumor lysis syndrome – in an elderly patient with primary refractory ALK-negative anaplastic large cell lymphoma with massive eosinophilia.